Patient Perceived Barriers and Enablers to Medication Adherence in the Treatment of Depression: A Qualitative Study - Yuki Meng; Christopher Chiu; Mamta Kapoor; Shelly-Anne Li; Navaldeep Kaur; Patricia Marr; Debbie Kwan; Kori Leblanc; Catherine Ji; Christine Papoushek (Journal of Primary Care & Community Health)
Background: Depression affects approximately 280 million individuals globally and it is a leading cause of disability. Despite effective medication options, 50% of patients prematurely discontinue antidepressants within 6 months. We sought to understand patients’ perspectives regarding their needs and expectations related to antidepressants. Objectives: To identify and describe enablers and barriers that influence adult patients’ medication adherence in depression treatment and to explore patients’ educational needs on initiating or continuing antidepressant therapy. Methods: Qualitative descriptive study was conducted using individual, semi-structured interviews of adult patients with depression who were prescribed an antidepressant within 3 months of study recruitment at an urban primary care clinic in Toronto, Canada. Thirteen participants were interviewed. Interviews were recorded and transcribed verbatim for inductive thematic analysis. Results: Six themes emerged: safety and effectiveness of antidepressant, understanding of depression and its management, medication administration, healthcare experiences in the treatment of depression, and social influences and relationships. Barriers to adherence included adverse effects of antidepressants, preference for non-pharmacological therapies, uncertainty about therapeutic effects, and social stigma. In contrast, enablers were positive responses from antidepressants, fear of relapse, reminder aids, established routine, and a trusting patient-provider relationship. Participants desired access to reliable, evidence-based, and personalized educational information delivered through verbal, written, and digital formats to support antidepressant adherence. Conclusion: To overcome the identified barriers, educational strategies should involve both patients and their prescribers to identify patient-specific needs and treatment goals, engage in shared decision-making, and maintain consistent follow-up to support antidepressant adherence.